Over time variation in microsatellite (ssr) patterns in a natural wild potato population from northwest Argentina. - Leofanti, Gabriela (2021)
The common potato, Solanum tuberosum L. (2n = 4x = 48), has 100–200 related wild taxonomic species endemic to the Americas, which constitute invaluable sources of genetic diversity. They form a polyploid series with 2n = 2x‐6x (x = 12), and can reproduce asexually by tubers and stolons and/or sexually by seeds. Information is scarce on their preponderant mode of reproduction, and its consequences on the genetic population structure over time. In previous work, a morphologically variable wild potato population from NW Argentina was sampled in two consecutive years. Two populations were ex situ regenerated from the sampled propagules (seeds in 2013 and tubers in 2014) for morphological and reproductive studies; these populations exhibited differences in reproductive behavior that could not be related to morphological phenotypes. To ascertain if the observed differences could be related to the captured genetic diversity in each year, a molecular analysis was carried out with seven microsatellite primer pairs located in seven chromosomes of the basic set. The captured genetic diversity, based on the proportion of individuals with a unique pattern of amplified fragments, varied significantly (χ2 α = 0.05) between sampling years. This could be possibly due to changes in the preponderant mode of reproduction, differential genotype fitness resulting from GxE interactions, or both. Wild potato accessions at germplasm banks are one‐time collection samples, thus, they may not be representative of the genetic diversity of the sampled population. To properly ex situ conserve the available genetic diversity, it is advisable to resample the sites whenever possible, and to conform each accession with the successive samples.